A Potent Postentry Restriction to Primate Lentiviruses in a Yinpterochiropteran Bat - James H. Morrison; Caitlin Miller; Laura Bankers; Gary Crameri; Lin-Fa Wang; Eric M. Poeschla (mBio, 2020)
ABSTRACT Bats are primary reservoirs for multiple lethal human viruses, such as Ebola, Nipah, Hendra, rabies, severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome-related coronavirus (MERS-CoV), and, most recently, SARS-CoV-2. The innate immune systems of these immensely abundant, anciently diverged mammals remain insufficiently characterized. While bat genomes contain many endogenous retroviral elements indicative of past exogenous infections, little is known about restrictions to extant retroviruses. Here, we describe a major postentry restriction in cells of the yinpterochiropteran bat Pteropus alecto. Primate lentiviruses (HIV-1, SIVmac) were potently blocked at early life cycle steps, with up to 1,000-fold decreases in infectivity. The block was specific, because nonprimate lentiviruses such as equine infectious anemia virus and feline immunodeficiency virus were unimpaired, as were foamy retroviruses. Interspecies heterokaryons demonstrated a dominant block consistent with restriction of incoming viruses. Several features suggested potential TRIM5 (tripartite motif 5) or myxovirus resistance protein 2 (MX2) protein restriction, including postentry action, cyclosporine sensitivity, and reversal by capsid cyclophilin A (CypA) binding loop mutations. Viral nuclear import was significantly reduced, and this deficit was substantially rescued by cyclosporine treatment. However, saturation with HIV-1 virus-like particles did not relieve the restriction at all. P. alecto TRIM5 was inactive against HIV-1 although it blocked the gammaretrovirus N-tropic murine leukemia virus. Despite major divergence in a critical N-terminal motif required for human MX2 activity, P. alecto MX2 had anti-HIV activity. However, this did not quantitatively account for the restriction and was independent of and synergistic with an additional CypA-dependent restriction. These results reveal a novel, specific restriction to primate lentiviruses in the Pteropodidae and advance understanding of bat innate immunity. IMPORTANCE The COVID-19 pandemic suggests that bat innate immune systems are insufficiently characterized relative to the medical importance of these animals. Retroviruses, e.g., HIV-1, can be severe pathogens when they cross species barriers, and bat restrictions corresponding to retroviruses are comparatively unstudied. Here, we compared the abilities of retroviruses from three genera (Lentivirus, Gammaretrovirus, and Spumavirus) to infect cells of the large fruit-eating bat P. alecto and other mammals. We identified a major, specific postentry restriction to primate lentiviruses. HIV-1 and SIVmac are potently blocked at early life cycle steps, but nonprimate lentiviruses and foamy retroviruses are entirely unrestricted. Despite acting postentry and in a CypA-dependent manner with features reminiscent of antiretroviral factors from other mammals, this restriction was not saturable with virus-like particles and was independent of P. alecto TRIM5, TRIM21, TRIM22, TRIM34, and MX2. These results identify a novel restriction and highlight cyclophilin-capsid interactions as ancient species-specific determinants of retroviral infection.